Justification of sorption composite usage on the basis of nanodisperse silica for sepsis prevention in complex treatment of purulent-inflammatory processes - Viltsaniuk, O. A.; Belyaev, P. V.; Osolodchenko, T. P.; Viltsaniuk, O. O. (Modern medical technology, 2019)
Introduction. The problem of purulentinflammatory processes treatment and the prevention of sepsis remains one of the most pressing problems of surgery. Purpose of the study. Is to estimate the effectiveness of sorption composition with antimicrobial properties on the basis of nanodisperse silica on the adhesive properties of microorganisms and to substantiate the expediency of its use for the purulent and inflammatory processes treatment and prevention of sepsis. Materials and methods. To determine the antimicrobial activity and the influence of the antiseptics of decasan, myramistin, ethonium, chlorhexidine and the sorption on the microorganisms adhesion properties composition was used the method of diffusion in agar of the museum strains of microorganisms S. Aureus ATCC 25923, E. Coli ATCC 25922, R. Vulgaris 4636, R. Aureginosa ATCC 27853, S. AIbicans 855/653, SI. Perfringens 28, Peptostreptococcus anaerobicus 22, Bacteroides fragilis 13/83, and clinical strains of S. Aureus, R. Aeuroginosa, E. Coli. Adhesive properties of microorganisms were studied according to the Brillis method et al. (1986) with the subsequent statistical processing of the data. Results. Studies have shown that antiseptics have high antimicrobial activity and reduce the adhesion ability of microorganisms. But the use of only antiseptics or only antibiotics for the purification of purulent foci can lead to toxins absorption and tissue decay products from purulent foci. That processes could be the trigger mechanism for sepsis development. The sorption composition is able to reduce the adhesive activity of bacteria, allows to absorb toxic substances from pathological foci, what preventing their resorption and thereby prevent the development of sepsis. Conclusions. The composition made from sorbents and antiseptics is not inferior to antimicrobial activity to antiseptics, which can reduce the virulence of bacteria, by reducing their adhesive activity, and absorb toxins of microorganisms and tissue decomposition products on their surface, thus prevent their absorption, which will prevent the purulent-inflammatory process progression and sepsis development.